theorem expr (a: nat) {x y: nat}: $ E. x E. y a = x, y $;
Step | Hyp | Ref | Expression |
---|---|---|---|
1 |
_1 = a -> _1 = a |
||
2 |
_1 = a -> x, y = x, y |
||
3 |
_1 = a -> (_1 = x, y <-> a = x, y) |
||
4 |
_1 = a -> (E. y _1 = x, y <-> E. y a = x, y) |
||
5 |
_1 = a -> (E. x E. y _1 = x, y <-> E. x E. y a = x, y) |
||
6 |
_1 = 0 -> _1 = 0 |
||
7 |
_1 = 0 -> x, y = x, y |
||
8 |
_1 = 0 -> (_1 = x, y <-> 0 = x, y) |
||
9 |
_1 = 0 -> (E. y _1 = x, y <-> E. y 0 = x, y) |
||
10 |
_1 = 0 -> (E. x E. y _1 = x, y <-> E. x E. y 0 = x, y) |
||
11 |
_1 = a1 -> _1 = a1 |
||
12 |
_1 = a1 -> x, y = x, y |
||
13 |
_1 = a1 -> (_1 = x, y <-> a1 = x, y) |
||
14 |
_1 = a1 -> (E. y _1 = x, y <-> E. y a1 = x, y) |
||
15 |
_1 = a1 -> (E. x E. y _1 = x, y <-> E. x E. y a1 = x, y) |
||
16 |
_1 = suc a1 -> _1 = suc a1 |
||
17 |
_1 = suc a1 -> x, y = x, y |
||
18 |
_1 = suc a1 -> (_1 = x, y <-> suc a1 = x, y) |
||
19 |
_1 = suc a1 -> (E. y _1 = x, y <-> E. y suc a1 = x, y) |
||
20 |
_1 = suc a1 -> (E. x E. y _1 = x, y <-> E. x E. y suc a1 = x, y) |
||
21 |
0, 0 = 0 |
||
22 |
x = 0 -> y = 0 -> x, y = 0, 0 |
||
23 |
x = 0 /\ y = 0 -> x, y = 0, 0 |
||
24 |
x = 0 /\ y = 0 -> 0, 0 = x, y |
||
25 |
x = 0 /\ y = 0 -> 0 = x, y |
||
26 |
x = 0 -> E. y 0 = x, y |
||
27 |
E. x E. y 0 = x, y |
||
28 |
m = x /\ n = y -> m = x |
||
29 |
m = x /\ n = y -> n = y |
||
30 |
m = x /\ n = y -> m, n = x, y |
||
31 |
m = x /\ n = y -> (suc a1 = m, n <-> suc a1 = x, y) |
||
32 |
m = x -> (E. n suc a1 = m, n <-> E. y suc a1 = x, y) |
||
33 |
E. m E. n suc a1 = m, n <-> E. x E. y suc a1 = x, y |
||
34 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> a1 = x, y |
||
35 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> suc a1 = suc (x, y) |
||
36 |
(x + y) * suc (x + y) // 2 + suc y = suc ((x + y) * suc (x + y) // 2 + y) |
||
37 |
conv pr |
(x + y) * suc (x + y) // 2 + suc y = suc (x, y) |
|
39 |
2 != 0 |
||
40 |
2 * ((x + y) * suc (x + y) // 2 + suc y) = 2 * (suc y * suc (suc y) // 2) <-> (x + y) * suc (x + y) // 2 + suc y = suc y * suc (suc y) // 2 |
||
41 |
2 * ((x + y) * suc (x + y) // 2 + suc y) = 2 * ((x + y) * suc (x + y) // 2) + 2 * suc y |
||
44 |
2 || suc y * suc (suc y) |
||
45 |
2 * (suc y * suc (suc y) // 2) = suc y * suc (suc y) |
||
47 |
suc y * suc (suc y) = suc (suc y) * suc y |
||
48 |
eqtr* |
2 * (suc y * suc (suc y) // 2) = suc (suc y) * suc y |
|
50 |
2 || (x + y) * suc (x + y) |
||
51 |
2 * ((x + y) * suc (x + y) // 2) = (x + y) * suc (x + y) |
||
52 |
0 + y = y |
||
53 |
a1 = x, y /\ x = 0 -> x = 0 |
||
54 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> x = 0 |
||
55 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> x + y = 0 + y |
||
56 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> x + y = y |
||
57 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> suc (x + y) = suc y |
||
58 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> (x + y) * suc (x + y) = y * suc y |
||
59 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> 2 * ((x + y) * suc (x + y) // 2) = y * suc y |
||
60 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> 2 * ((x + y) * suc (x + y) // 2) + 2 * suc y = y * suc y + 2 * suc y |
||
61 |
(y + 2) * suc y = y * suc y + 2 * suc y |
||
64 |
y + suc 1 = suc (y + 1) |
||
65 |
conv d2 |
y + 2 = suc (y + 1) |
|
68 |
y + 1 = suc y |
||
69 |
suc (y + 1) = suc (suc y) |
||
70 |
eqtr* |
y + 2 = suc (suc y) |
|
71 |
(y + 2) * suc y = suc (suc y) * suc y |
||
72 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> (y + 2) * suc y = suc (suc y) * suc y |
||
73 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> y * suc y + 2 * suc y = suc (suc y) * suc y |
||
74 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> 2 * ((x + y) * suc (x + y) // 2) + 2 * suc y = suc (suc y) * suc y |
||
75 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> 2 * ((x + y) * suc (x + y) // 2) + 2 * suc y = 2 * (suc y * suc (suc y) // 2) |
||
76 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> 2 * ((x + y) * suc (x + y) // 2 + suc y) = 2 * (suc y * suc (suc y) // 2) |
||
77 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> (x + y) * suc (x + y) // 2 + suc y = suc y * suc (suc y) // 2 |
||
78 |
suc y * suc (suc y) // 2 + 0 = suc y * suc (suc y) // 2 |
||
79 |
suc y + 0 = suc y |
||
80 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> m = suc y |
||
81 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> n = 0 |
||
82 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> m + n = suc y + 0 |
||
83 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> m + n = suc y |
||
84 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> suc (m + n) = suc (suc y) |
||
85 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> (m + n) * suc (m + n) = suc y * suc (suc y) |
||
86 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> (m + n) * suc (m + n) // 2 = suc y * suc (suc y) // 2 |
||
87 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> (m + n) * suc (m + n) // 2 + n = suc y * suc (suc y) // 2 + 0 |
||
88 |
conv pr |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> m, n = suc y * suc (suc y) // 2 + 0 |
|
89 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> m, n = suc y * suc (suc y) // 2 |
||
90 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> (x + y) * suc (x + y) // 2 + suc y = m, n |
||
91 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> suc (x, y) = m, n |
||
92 |
a1 = x, y /\ x = 0 /\ m = suc y /\ n = 0 -> suc a1 = m, n |
||
93 |
a1 = x, y /\ x = 0 /\ m = suc y -> E. n suc a1 = m, n |
||
94 |
a1 = x, y /\ x = 0 -> E. m E. n suc a1 = m, n |
||
95 |
a1 = x, y -> x = 0 -> E. m E. n suc a1 = m, n |
||
96 |
x != 0 <-> E. z x = suc z |
||
97 |
conv ne |
~x = 0 <-> E. z x = suc z |
|
98 |
a1 = x, y -> suc a1 = suc (x, y) |
||
99 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> suc a1 = suc (x, y) |
||
100 |
suc z + y = z + suc y |
||
101 |
x = suc z -> x + y = suc z + y |
||
102 |
a1 = x, y /\ x = suc z -> x + y = suc z + y |
||
103 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> x + y = suc z + y |
||
104 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> x + y = z + suc y |
||
105 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> m = z |
||
106 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> n = suc y |
||
107 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> m + n = z + suc y |
||
108 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> x + y = m + n |
||
109 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> suc (x + y) = suc (m + n) |
||
110 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> (x + y) * suc (x + y) = (m + n) * suc (m + n) |
||
111 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> (x + y) * suc (x + y) // 2 = (m + n) * suc (m + n) // 2 |
||
112 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> suc y = n |
||
113 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> (x + y) * suc (x + y) // 2 + suc y = (m + n) * suc (m + n) // 2 + n |
||
114 |
conv pr |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> (x + y) * suc (x + y) // 2 + suc y = m, n |
|
115 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> suc (x, y) = m, n |
||
116 |
a1 = x, y /\ x = suc z /\ m = z /\ n = suc y -> suc a1 = m, n |
||
117 |
a1 = x, y /\ x = suc z /\ m = z -> E. n suc a1 = m, n |
||
118 |
a1 = x, y /\ x = suc z -> E. m E. n suc a1 = m, n |
||
119 |
a1 = x, y -> E. z x = suc z -> E. m E. n suc a1 = m, n |
||
120 |
a1 = x, y -> ~x = 0 -> E. m E. n suc a1 = m, n |
||
121 |
a1 = x, y -> E. m E. n suc a1 = m, n |
||
122 |
E. y a1 = x, y -> E. m E. n suc a1 = m, n |
||
123 |
E. x E. y a1 = x, y -> E. m E. n suc a1 = m, n |
||
124 |
E. x E. y a1 = x, y -> E. x E. y suc a1 = x, y |
||
125 |
E. x E. y a = x, y |